Computer aided analysis of planar linkage mechanisms / Zuhairi Abd Wahab and Sazali Kemin - Abd Wahab, Zuhairi; Kemin, Sazali (1990)
The main objective of this project is to prepare a suitable program on kinematic analysis of planar four bar linkage and planar slider crank mechanisms. These mechanisms have been selected because they form the basic elements of most machines and because they are easily adaptable to the teaching of fundamental kinematic principles. Once these principles are fully understood, it is comparatively easy to apply them to the analysis of more complex mechanisms. The computer programs listed in this report are based on vector method and calculus method. The programs are written in FORTRAN LANGUAGE. Throughout our work, we try as much as possible to make these programs simpler and easy to be understood. To apply these programs, typically, the link lengths of the mechanism, the crank angle and the angular velocity must be known. From these data, the required velocities and accelerations can be computed for any specified angular position of the crank in its motion cycle.